Electrophysiological Mechanisms of Brugada Syndrome: Insights from Pre-clinical and Clinical Studies - Tse, Gary; Liu, Tong; Li, Ka H. C.; Laxton, Victoria; Chan, Yin W. F.; Keung, Wendy; Li, Ronald A.; Yan, Bryan P. (Frontiers in Physiology, 2016)
Brugada syndrome (BrS), is a primary electrical disorder predisposing affected individuals to sudden cardiac death via the development of ventricular tachycardia and fibrillation (VT/VF). Originally, BrS was linked to mutations in the SCN5A, which encodes for the cardiac Na+ channel. To date, variants in 19 genes have been implicated in this condition, with 11, 5, 3 and 1 genes affecting the Na+, K+, Ca2+ and funny currents, respectively. Diagnosis of BrS is based on ECG criteria of coved- or saddle-shaped ST segment elevation and/or T-wave inversion with or without drug challenge. Three hypotheses based on abnormal depolarization, abnormal repolarization and current-load-mismatch have been put forward to explain the electrophysiological mechanisms responsible for BrS. Evidence from computational modelling, pre-clinical and clinical studies illustrates that molecular abnormalities found in BrS lead to alterations in excitation wavelength (λ), which ultimately elevates arrhythmic risk. A major challenge for clinicians in managing this condition is the difficulty in predicting the subset of patients who will suffer from life-threatening VT/VF. Several repolarization risk markers have been used thus far, but these neglect the contributions of conduction abnormalities in the form of slowing and dispersion. Indices incorporating both repolarization and conduction and based on the concept of λ have recently been proposed. These may have better predictive values than the existing markers. Current treatment options are pharmacotherapy to reduce the occurrence of VT/VF or to abort these episodes, and interventions include implantable cardioverter-defibrillator insertion or radiofrequency ablation of abnormal arrhythmic substrate.